2007
DOI: 10.1007/s10549-007-9685-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk of needle tract seeding of breast cancer: cytological results derived from core wash material

Abstract: Needle track seeding has been recognized as a possible, albeit rare, complication of breast core needle biopsy. The purpose of this study was to assess the risk of needle tract seeding of breast cancer from cytological results derived from core needle wash material. The study included biopsies of 207 breast cancers performed using ultrasonographically guided 18-gauge core needles. Each core needle without exposed sample notch was washed in saline solution immediately after removing the needles. Cytology derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…In benign tumors the cohesiveness of the tissue and cells is much higher than in malignant lesions. 7,11 In our study, the histological benign diagnosis on touch imprint or core wash cytology was noticed as benign or atypia favoring benign. Our study showed slight differences between core wash and touch imprint in figures.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…In benign tumors the cohesiveness of the tissue and cells is much higher than in malignant lesions. 7,11 In our study, the histological benign diagnosis on touch imprint or core wash cytology was noticed as benign or atypia favoring benign. Our study showed slight differences between core wash and touch imprint in figures.…”
mentioning
confidence: 51%
“…8 Others use the technique to investigate the possibility of needle tract seeding. 11 Still, touch imprint is mostly used for providing a preliminary diagnosis. The sensitivity ranged from 74%-95%, whereas specificity ranged from 97%-100%.…”
mentioning
confidence: 99%
“…CNB is more invasive, time consuming, has a higher rate of complications, and has a greater cost for both the biopsy equipment and the required histopathological laboratory processing and reporting [16, 21, 22]. There are reports of a risk of track seeding by carcinoma [23], and of a possible worse prognosis after CNB [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies suggest that FNA can rarely cause needle track seeding or cutaneous metastasis at Biopsy Site in renal, pancreatic and hepatic (primary or metastatic) cancers [9][10][11]. As well, a few cases of breast cancer with the same complication after CNB have been reported [12,13]. There are also studies implying that procedures like prostate biopsy or surgical removal of the tumor during a colonoscopy (in colorectal cancer) may increase the number of circulating tumor cells (CTCs) in the blood in some cases [14,15].…”
Section: Surgical Biopsymentioning
confidence: 99%